Analysis of e-puskesmas satisfaction level using pieces framework at belimbing public health center padang - Yuli Mardi; Syamsul Kamal (Jurnal Mantik, 2023)
To determine the extent of the impact of the E-Puskesmas application on the business processes at Bellimbing public health center Padang, an analysis of the existing system is necessary. The analysis of the E-Puskesmas application is conducted using the PIECES framework. The PIECES framework is a method used to identify and analyze critical aspects that can affect the utilization of a system or application, consisting of Performance, Information, Economy, Control, Efficiency, Security, and Service. This method is employed in various contexts, including information system development, evaluation of existing systems, and business process improvement. This research is conducted quantitatively by distributing questionnaires to E-Puskesmas users. The results of the analysis of the E-Puskesmas application's usage across the six PIECES parameters indicate that, on average, users are satisfied with the application that has been in use for over a year at Belimbing public health center